2010
DOI: 10.1186/1756-6606-3-19
|View full text |Cite
|
Sign up to set email alerts
|

Rab-mediated vesicular transport is required for neuronal positioning in the developing Drosophila visual system

Abstract: Background: The establishment of tissue architecture in the nervous system requires the proper migration and positioning of newly born neurons during embryonic development. Defects in nuclear translocation, a key process in neuronal positioning, are associated with brain diseases such as lissencephaly in humans. Accumulated evidence suggests that the molecular mechanisms controlling neuronal movement are conserved throughout evolution. While the initial events of neuronal migration have been extensively studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Whether the defect in forward nuclear movement of migrating neurons is secondary to the abnormal adhesion or whether Rab5 and Rab11 directly regulate nuclear movement is still unclear. A very recent report showed that Rab5 and Rab11 are required for maintaining apical localization of the nuclei in Drosophila photoreceptor cells, 30 suggesting that Rab5-and Rab11-dependent pathways might be directly involved in nuclear movement.…”
Section: Rab11 and Rab7 Regulate Distinct Steps Of Neuronal Migrationmentioning
confidence: 99%
“…Whether the defect in forward nuclear movement of migrating neurons is secondary to the abnormal adhesion or whether Rab5 and Rab11 directly regulate nuclear movement is still unclear. A very recent report showed that Rab5 and Rab11 are required for maintaining apical localization of the nuclei in Drosophila photoreceptor cells, 30 suggesting that Rab5-and Rab11-dependent pathways might be directly involved in nuclear movement.…”
Section: Rab11 and Rab7 Regulate Distinct Steps Of Neuronal Migrationmentioning
confidence: 99%
“…While the role of Rab6 in membrane trafficking is well established, very few GAPs or GEFs for Rab6 have been identified; thus their physiological importance is largely unknown. The physiological roles of RabGAPs were addressed only recently in flies (Houalla et al 2010;Uytterhoeven et al 2011) and worms (Chotard et al 2010). In those cases, removing the function of the RabGAPs produced phenotypes almost identical to those of removing the relevant Rabs, showing the fundamental roles of RabGAPs in modulating Rab functions.…”
mentioning
confidence: 99%
“…Lsp2 is a subunit of the Drosophila hexamerin protein; it functions during differentiation of the mosquito larval–pupa l stage [ 33 ]. The RN-tre gene product is thought to interact with Rab5 and Rab11 to regulate apical localization of the R-cell [ 34 ]. Ets family members are expressed in Drosophila oocytes and larvae, and are involved in cell migration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%